Holding Period of the Energy Sector: Market Value Factor, Bid-Ask Spreads, and Variance Return - Abdul Latif*; Wiyarno Wiyarno; Erna Apriani (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
The level of investor confidence in a company going public is by holding the company's shares for a long time, which improves the holding period of a share. Especially during a pandemic, it is a significant record for companies going public to maintain a reputation for their performance towards investors. During the pandemic, the energy sector became the target of investors because consumer levels increased sharply during the pandemic. This phenomenon makes the holding period in the energy sector worthy of research. Thus this study aims to analyze the effect of market value on the energy sector holding period, bid-ask spreads on the energy sector holding period, and variance return on the energy sector holding period. The data used in this study is secondary data in the form of data on the number of outstanding shares, daily data on the volume of stock trading transactions, the bid price and ask price of shares, and the average stock return of energy sector companies during 2021 with cross-sectional data types. The population and sample in this study are all go-public companies that belong to the energy sector on the Indonesian stock exchange, namely 76 companies on all accelerator boards with a period of 2021. The data analysis tool used is a multiple linear regression model to influence market value, bid-ask spreads, and variance returns in the energy sector holding period. The results of this study show that the market value variable has a positive effect on the holding period, and for the results of the bid-ask spreads variable, the variance return does not affect the holding period.